Egg consumption and risk of type 2 diabetes: findings from 3 large US cohort studies of men and women and a systematic review and meta-analysis of prospective cohort studies. Issue 3 (26th May 2020) - Drouin-Chartier, Jean-Philippe; Schwab, Amanda L; Chen, Siyu; Li, Yanping; Sacks, Frank M; Rosner, Bernard; Manson, JoAnn E; Willett, Walter C; Stampfer, Meir J; Hu, Frank B; Bhupathiraju, Shilpa N
ABSTRACT: Background: Whether egg consumption is associated with the risk of type 2 diabetes (T2D) remains unsettled. Objectives: We evaluated the association between egg consumption and T2D risk in 3 large US prospective cohorts, and performed a systematic review and meta-analysis of prospective cohort studies. Methods: We followed 82, 750 women from the Nurses' Health Study (NHS; 1980–2012), 89, 636 women from the NHS II (1991–2017), and 41, 412 men from the Health Professionals Follow-up Study (HPFS; 1986–2016) who were free of T2D, cardiovascular disease, and cancer at baseline. Egg consumption was assessed every 2–4 y using a validated FFQ. We used Cox proportional hazard models to estimate HRs and 95% CIs. Results: During a total of 5, 529, 959 person-years of follow-up, we documented 20, 514 incident cases of T2D in the NHS, NHS II, and HPFS. In the pooled multivariable model adjusted for updated BMI, lifestyle, and dietary confounders, a 1-egg/d increase was associated with a 14% (95% CI: 7%, 20%) higher T2D risk. In random-effects meta-analysis of 16 prospective cohort studies (589, 559 participants; 41, 248 incident T2D cases), for each 1 egg/d, the pooled RR of T2D was 1.07 (95% CI: 0.99, 1.15; I 2  = 69.8%). There were, however, significant differences by geographic region ( P for interaction = 0.01). Each 1 egg/d was associated with higher T2D risk among US studies (RR: 1.18; 95% CI: 1.10, 1.27; I 2  = 51.3%), but not among European (RR: 0.99; 95% CI: 0.85, 1.15; I 2  = 73.5%) or Asian (RR: 0.82; 95% CI: 0.62, 1.09; I 2  = 59.1%) studies. Conclusions: Results from the updated meta-analysis show no overall association between moderate egg consumption and risk of T2D. Whether the heterogeneity of the associations among US, European, and Asian cohorts reflects differences in egg consumption habits warrants further investigation. This systematic review was registered at www.crd.york.ac.uk/prospero as CRD42019127860.